2016
DOI: 10.1038/aps.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Over-expressed human TREK-1 inhibits CHO cell proliferation via inhibiting PKA and p38 MAPK pathways and subsequently inducing G1 arrest

Abstract: TREK-1 overexpression suppresses CHO cell proliferation by inhibiting the activity of PKA and p38/MAPK signaling pathways and subsequently inducing G1 phase cell arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Previous studies have shown the close correlation between the pathological process of ischemic stroke and the levels of TREK-1 mRNA and protein expressions [31, 32]. Although the mechanism by which TREK-1 expression affects cellular functions remains unclear, it is believed, under hypoxic conditions, that the upregulation of TREK-1 expression inhibits the activity of protein kinase A and the expression of cyclin D1 [33] and decreases neuronal stem cell [34], astrocyte [35], and human osteoblasts proliferation [35, 36]. Recently, it has been demonstrated that l-NBP promotes neurogenesis and tissue recovery through inhibition of TREK-1 channels [37].…”
Section: Nbp and Ischemic Strokementioning
confidence: 99%
“…Previous studies have shown the close correlation between the pathological process of ischemic stroke and the levels of TREK-1 mRNA and protein expressions [31, 32]. Although the mechanism by which TREK-1 expression affects cellular functions remains unclear, it is believed, under hypoxic conditions, that the upregulation of TREK-1 expression inhibits the activity of protein kinase A and the expression of cyclin D1 [33] and decreases neuronal stem cell [34], astrocyte [35], and human osteoblasts proliferation [35, 36]. Recently, it has been demonstrated that l-NBP promotes neurogenesis and tissue recovery through inhibition of TREK-1 channels [37].…”
Section: Nbp and Ischemic Strokementioning
confidence: 99%
“…We focused our attention in a novelty promising target such as the voltage‐gated potassium channels, K V , which are present in tumor cells, and they play important roles in the regulation of tumor cell proliferation, cell cycle progression, migration, and apoptosis (Chittajallu et al., ; Comes et al., ; Fukushiro‐Lopes et al., ; Han et al., ; Lang et al., ; Ouadid‐Ahidouch & Ahidouch, ; Pardo, ; Pardo et al., ; Sauter et al., ; Stuhmer et al., ; Wang, ; Wonderlin et al., ; Zhang et al., ). The modulation of potassium channels has been identified as target for some 4‐substituted quinolines and 4‐substituted quinolin‐2‐ones (Dinsmore & Bergman, ; Galanakis et al., ; Hewawasam et al., , ; Kang et al., ; Wulff et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…SKBr3 cancer cell was used to perform this assay. It is well documented that several voltage‐gated K+ channels of the Shaker family (K V ) are present in breast cancer tissue or cell lines (Fukushiro‐Lopes et al., ; Han et al., ; Sauter et al., ; Stuhmer et al., ; Zhang et al., ). Results are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations